The Unit of Translation: Statistics Speak - Huang, Harry; Wu, Canzhong (Meta, 2009)
AbstractThe authors have conducted a study aiming at determining the unit of translation (UT), a subject of debate for more than forty years. The article consists of a review of relevant literature, a redefinition of the UT, an examination of sampled translated texts, excerpts and sentences of over 23,000 pages, including the Bible and Soul Mountain, translated from the Nobel Prize-winning novel of the Chinese author, Gao Xingjian, and an international survey. The contrastive analysis of these ST and TT materials shows that translations are done sentence by sentence within context and thus identifies the sentence in context as the UT. This identification is further confirmed by an international survey of 66 professional translators and translation editors. By verifying the UT, this study indicates that for a UT-related theory to be testable, the translation theorist should no longer ignore or sideline the sentence from its context.